Modeling and Optimization of Electric Discharge Machining Performances using Harmony Search Algorithm (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Electric Discharge Machining (EDM) is one of the widely used non-conventional machining processes for complex and difficult-to-machine materials. EDM technology has been improve significantly and has been developed in many ideas especially in the manufacturing industries that yielded enormous benefits in economic as well as generating keen interest in research area. A major issue in EDM process is how to obtain accurate results of the machining performance measurement value at optimal point of cutting conditions. Thus, this study proposed harmony search algorithm approach for optimization of surface roughness (Ra) in die sinking electric discharge machining (EDM). The mathematical model was developed using regression analysis based on four machining parameters which are pulse on time, peak current, servo voltage and servo speed. The result shows that the optimal solutions for Ra can be found with the minimum values of 1.3031 Âµm.
Keywords: Harmony Search; Regression; Electric Discharge Machining; Surface Roughness; Electrode Wear Rate